STUDENTS’ FINANCIAL BEHAVIOR IN THE DIGITAL ERA: THE ROLE OF FINANCIAL LITERACY, SELF-CONTROL, FINTECH, AND SOCIAL ENVIRONMENT - Melia Widyarti; Erida Herlina (Center for Indonesian Accounting Studies, 2025)
Research Objective - This research aims to analyze the influence of financial literacy, self-control, financial technology, and the social environment on students' financial behavior in Surabaya. Method – The Research method uses a quantitative approach, with primary data collected through questionnaires distributed to students at several universities in Surabaya, using purposive sampling. The number of samples used in this study was 180 students. Data analysis was carried out using the Partial Least Squares (PLS). Findings - The study's results show that financial literacy, self-control, and the social environment affect students' financial behavior. Meanwhile, financial technology does not influence students' financial behavior. Theoretical and Policy Implications - This research suggests that improving financial literacy and self-control, coupled with the wise use of financial technology and a supportive social environment, are crucial for shaping healthy financial behavior among students. Therefore, suggested solutions include strengthening financial literacy education in higher education, controlling the use of FinTech, and creating a social environment that encourages responsible financial management. Research Novelty - The novelty of this research lies in analyzing the role of financial technology as a modern contextual factor in shaping students' financial behavior.